Dynamic demographic analysis - Schoen,Robert (New York Springer Berlin Heidelberg, 2016)
This volume presents state of the art analyses from scholars dealing with a range of demographic topics of current concern, including longevity, mortality and morbidity, migration, and how population composition impacts intergenerational transfer schemes.
Part I. Analyzing dynamic fertility -- Part II. Dynamic mortality and morbidity -- Part III. Analyzing heterogeneity -- Part IV. Extending stationary and stable population analysis -- Part V. The dynamics of population size and structure -- Part VI. The age-period-cohort problem.
Keywords: Social sciences; Mathematics; Statistics